Attitudes and knowledge held about the role of the paediatrician in cases of child sexual abuse (CSA): a comparison between the police, paediatricians and social workers. (4th April 2011) - Rachamim, E S; Hodes, D
Abstract : Aims: Research estimates that up to 15% of children experience sexual abuse and perhaps as little as half of children with suspected child sexual abuse (CSA) are offered a paediatric consultation (D Hodes, R Sundrum, GL Laing, Do Child Protection Teams Refer Children with Alleged Sexual Abuse for Medical Consultation? London Borough of City and Hackney, 1999, unpublished data). Is this because the professional's view is that the paediatricians' examination of children is in itself abusive? Is it due to inadequate training and knowledge? To investigate further, surveys were sent to police, paediatric registrars and social workers (SWs). Methods: The anonymised online survey was sent to; police officers of all ranks working in the five CAIT and Sapphire teams in North London, to all registrars (ST4+) within London and to all levels of SWs in Children's Social Care within 5 boroughs in North London. Results: 62% of police, 87% of registrars and 65% of SWs wanted more information on the role of the paediatrician in the CSA assessment (table 1). Registrars thought the theory was covered but the practical aspects were not well taught; some would like compulsory training, leaflets or to be on the Haven rota. There was confusion about the forensic aspects and the actual examination among all groups but in particular the police. 50% of police would be deterred from referral to a paediatrician if no intimate body swabs were available and 1/3 would not refer alleged 'touching' without penetration, despite other benefits such as reassurance, follow-up, diagnosing STIs and identifying emotional, developmental or medical problems. 38% of police, 12% of SWs and 20% of registrars felt the assessment re-enacted the abuse and similar numbers felt it was harmful and painful. Conclusions: This multi-agency research has increased our understanding of factors influencing referral patterns, attitudes and knowledge about the role of the paediatrician in cases of CSA and has highlighted the training needs of three professional groups. Most police and SWs had positive experiences working with paediatricians, but health professionals need to contribute to strategy and other discussions and training. In order to benefit the child, further joint training will improve our working relationships.